CONSERVATION AGRICULTURE PRACTICES IN PERENNIAL HORTICULTURAL CROPPING SYSTEMS TO IMPROVE SOIL HEALTH - RUPA T. R. (The Journal of Research, PJTSAU, 2023)
Conservation agriculture practices in perennial horticulture cropping systems aims to provide and maintain optimal conditions in the root-zone, ensure that water enters the soil, increase beneficial biological activity in the soil and avoid physical or chemical damage to roots and soil organisms that would disrupt their effective functioning.It is based on three principles viz., minimal mechanical soil disturbance; permanent soil cover through the preservation of crop residues and cover crops; and crop rotation. Conservation principles minimise soil disturbance and makes use of soil biological activity, practising crop rotations; using fertilizers as appropriate and relying on integrated pest and weed management in order to minimize damage to the environment and provide organic matter and nutrients.Conservation practices minimises nutrient losses through the appropriate use of deep-rooting cover crops that recycle nutrients leached from the topsoil, conserves soil moisture by minimising evaporation losses, enhancing infiltration and minimising surface runoff. Cover crops of variable rooting depths and root spread on the orchard floor offers little scope for the plant nutrients to be lost through leaching. Long-term soil conservation management in perennial horticultural crops improved the quality of soils through soil aggregates and water stability, enhancing soil microbial diversity, the organic carbon fraction, especially near the surface, lowered the soil bulk density and enhanced the infiltration rate, thereby contributed in increasing orchard crop productivity. Through conservation agriculture practices old and senile orchards can be revived. Conservation agriculture is now receiving global attention for its carbon sequestration potential.